You Are Here : Art After the Internet - Kholeif, Omar (Manchester; London; Home; Space, 2018)
Edited with text by Omar Kholeif. Foreword by Ed Halter. Texts by Sam Ashby, Basel Abbas, Ruanne Abu Rahme, Brad Troemel, James Bridle, Gne McHugh, Brian Droitcour, Michael Connor, Erika Balsom, Omar Kholeif, Zach Bas, Lucia Pietroiusti, Jennifer Chan, Sophia Al Maria, Stephanie Bailey, Jesse Darling, Constant Dullaart, Basak Senova. Projects: Tyler Coburn, Jamie Shovlin, Jeremy Bailey, Jon Rafman, Model Court, Basel Abbas & Ruanne Abou-Rahme, James Richards. You Are Here: Art After the Internet is the first major publication to critically explore both the effects and affects that the internet has had on contemporary artistic practices. Responding to an era that has increasingly chosen to dub itself as (3z(Bpost-internet,(3y (Bthis collective text explores the relationship of the internet to art practices from the early millennium to the present day. The book positions itself as a provocation on the current state of cultural production, relying on first-person accounts from artists, writers and curators as the primary source material. The book raises urgent questions about how we negotiate the formal, aesthetic and conceptual relationship of art and its effects after the ubiquitous rise of the internet.s
English
Keywords: Digital Age; Internet Age; N5300-7418 Visual Arts- History